2019
DOI: 10.1111/scs.12654
|View full text |Cite
|
Sign up to set email alerts
|

Cultural sensitivity in paediatric nursing care: a concept analysis using the Hybrid method

Abstract: Background Cultural sensitivity is a core concept to establish awareness and knowledge about various ethnicities, cultures, genders and additional diversity characteristics to understand individual's requests and respond appropriately to them. A need for further development of the concept is warranted, especially in the context of paediatric nursing. Aims The purpose of this paper was to determine the main elements of cultural sensitivity in the context of paediatric nursing in Iran. Methods The Hybrid method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 50 publications
0
7
0
1
Order By: Relevance
“…Culturally sensitive care is multifaceted and unique to each person's cultural identity, and in neonatal care settings, this might include being sensitive and adaptive to cultural differences, customs, traditions, and even dietary needs. 14 But being able to provide for parents' cultural needs requires health professionals to have an awareness of their own cultural beliefs, values, and attitudes first. [25][26][27] Of note, research conducted in Saudi Arabia, where the neonatal nursing workforce was culturally diverse, demonstrated that knowledge deficits in relation to parents' cultural needs can be overcome by prioritizing respect for others, an openness to cultural diversity and difference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Culturally sensitive care is multifaceted and unique to each person's cultural identity, and in neonatal care settings, this might include being sensitive and adaptive to cultural differences, customs, traditions, and even dietary needs. 14 But being able to provide for parents' cultural needs requires health professionals to have an awareness of their own cultural beliefs, values, and attitudes first. [25][26][27] Of note, research conducted in Saudi Arabia, where the neonatal nursing workforce was culturally diverse, demonstrated that knowledge deficits in relation to parents' cultural needs can be overcome by prioritizing respect for others, an openness to cultural diversity and difference.…”
Section: Discussionmentioning
confidence: 99%
“…3 The provision of culturally sensitive care is impeded when nurses have limited understanding of parental cultural needs. 14 Two studies demonstrate deficits in nursing knowledge in relation to cultural competence. A US survey of obstetric and neonatal nurses reported moderately high levels of cultural competence; however, scores for culturally competent behaviors were moderate, suggesting room for improvement in the provision of culturally sensitive care.…”
mentioning
confidence: 99%
“…A combination of key terms cultural and alienation was imputed to get a current consensus regarding the concept. Previous concept analyses on cultural competence, cultural sensitivity, and cultural humility 14–16 have been published; however, none have explored the concept of cultural alienation explicitly. Inclusion criteria were full text, peer‐reviewed, English language, and published within 5 years.…”
Section: Concept Analysis Methodsmentioning
confidence: 99%
“…Kultūrinio jautrumo bruožai yra žinios, dėmesys, supratimas, pagarba ir intervencijų optimizavimas, atsižvelgiant į pacientų kultūrinius poreikius. Kultūrinis jautrumas padeda slaugytojams suprasti, kaip pacientų požiūris ir pažiūros veikia jų elgesį Aghajari ir kt., 2019, Iranas [21] Tai sąvoka, apibrėžianti žmonių priėmimo tokių, kokie jie yra, savybę, su bendru požiūriu į nuolatinį tobulėjimą, leidžianti žmogui atskirti ir priimti skirtingas kultūras Perng, Watson, 2012, Taivanas [14] Tai slaugytojų supratimas apie kliento įsitikinimus, jo kultūros vertinimas ir pagarba jos įtakai kliento elgesiui…”
Section: Kultūrinis Jautrumasunclassified